Revisiting the Privacy Paradox: Transparency, Trust, and the Effectiveness of Behavioural Analytics in Digital Marketing - Yosef Dema; Elisabeth Vita Mutiarawati; Ari Hadi Prasetyo; Yohanes Langgar Billy (Jurnal Komunikasi dan Bisnis, 2026)
This study revisits the privacy paradox in data-driven marketing by examining whether privacy concerns constrain the effectiveness of behavioural analytics and whether transparency plays a more influential role in shaping consumer purchase decisions. Drawing on the Theory of Planned Behaviour, Privacy Calculus Theory, and research on algorithm aversion, behavioural analytics is conceptualized as a digital choice architecture that influences consumer decision-making. Survey data from 228 digitally active consumers were analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM). The results indicate that behavioural analytics positively influences purchase decisions, while privacy concerns do not significantly moderate this relationship, supporting the persistence of the privacy paradox. In contrast, transparency significantly strengthens the effect of behavioural analytics by enhancing consumer trust and perceived procedural fairness. These findings suggest that transparency, rather than privacy concern, is the key mechanism supporting effective personalization. From a managerial perspective, organizations should complement behavioural analytics with transparent data governance, explainable algorithmic practices, and clear communication regarding data use to strengthen consumer trust. This study advances digital marketing research by reframing the privacy paradox as a question of legitimacy and trust in responsible data-driven marketing.